2016
DOI: 10.2527/jas.2015-0061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quebracho tannin extract on rumen fermentation and yield and composition of microbial mass in heifers1

Abstract: To determine the effects of incremental quebracho tannin extract (QTE) infusions on rumen fermentation and yield and composition of microbial mass, a study was conducted that consisted of 1 control period (Control I) without QTE dosing; 4 periods when all animals received 1, 2, 4, or 6% QTE of the diet (DM basis); and a second control period (Control II). Each period consisted of 9 d of adaptation, 6 d of urine collection, and 1 d of rumen sampling. Three rumen-fistulated heifers (495 kg BW [SE 14]) were offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
3
11
1
Order By: Relevance
“…Higher CT concentrations in vivo decreased rumen NH 3 concentration up to 24% when L. corniculatus silage (7.3-9.5% dietary total CT) replaced M. sativa silage (0% dietary total CT) in a dairy cattle ration (Hymes-Fecht et al, 2013). A few studies however, have reported no effect of CT on ruminal NH 3 -N concentrations Dickhoefer et al, 2016). These results may be explained by CT source, lower water intake [i.e.…”
Section: Interactions Between Condensed Tannins and Protein In The Dietcontrasting
confidence: 39%
See 2 more Smart Citations
“…Higher CT concentrations in vivo decreased rumen NH 3 concentration up to 24% when L. corniculatus silage (7.3-9.5% dietary total CT) replaced M. sativa silage (0% dietary total CT) in a dairy cattle ration (Hymes-Fecht et al, 2013). A few studies however, have reported no effect of CT on ruminal NH 3 -N concentrations Dickhoefer et al, 2016). These results may be explained by CT source, lower water intake [i.e.…”
Section: Interactions Between Condensed Tannins and Protein In The Dietcontrasting
confidence: 39%
“…These results may be explained by CT source, lower water intake [i.e. lower NH 3 dilution as in Dickhoefer et al (2016)] or because energy availability was limiting for microbial growth. Christensen et al (2015) also reported no differences in rumen NH 3 -N concentration of lactating dairy cows after replacing 50 or 100% of M. sativa hay with L. corniculatus (0.51% CT).…”
Section: Interactions Between Condensed Tannins and Protein In The Dietmentioning
confidence: 87%
See 1 more Smart Citation
“…This shows the potential of tannins to reduce rumen microbial activity. Dickhoefer et al (2016) found a linear decline on urinary excretion, not only of uric acid but of allantoin as well. The difference may be due to the level of tannins, since these authors included tannins up to 6%.…”
Section: Urinary Parameters Microbial Protein and Nitrogen Balancementioning
confidence: 88%
“…Using diets of up to 6% of tannins, Ahnert et al (2015) found a linear reduction in urinary N and a linear increase in faecal N, and, regardless the level of tannins in diets, N retention was higher with tannins than without. The urinary purine derivatives declined linearly when tannins were increased up to 6% in the study of Dickhoefer et al (2016).…”
Section: Introductionmentioning
confidence: 92%